A Case of Thyroid Storm Associated with Cardiomyopathy and Poststreptococcal Glomerulonephritis - Lisa J. Underland; Gerson A. Vallencia Villeda; Abhijeet Pal; Leslie Lam (Case Reports in Pediatrics)
Thyroid storm has a high mortality rate and is often associated with a precipitating factor such as intercurrent illness or infection. It is rare in pediatric patients. Cardiac disease in hyperthyroidism mostly manifests itself as tachycardia but more serious cardiac findings have also been described. A 5-year-old male with recent strep throat infection presented with dilated cardiomyopathy, hematuria, and symptoms and lab findings consistent with severe hyperthyroidism. He was diagnosed with thyroid storm secondary to concurrent Graves’ disease and poststreptococcal glomerulonephritis (PSGN). After starting the treatment with methimazole and a beta-blocker, his cardiac disease gradually improved and the PSGN resolved over time. There are no specific pediatric criteria for thyroid storm. Adult criteria can be difficult to apply to pediatric cases. Criteria for diagnosis of thyroid storm are less clear for pediatric patients. Dilated cardiomyopathy is a rare cardiac manifestation of hyperthyroidism. PSGN is due to glomerular immune complexes and can complicate group A strep infection. Providers should be aware of cardiac disease as a complication of hyperthyroidism. PSGN should not mechanistically be related to hyperthyroidism but can precipitate the signs of thyroid storm such as hypertension. This association has not been previously reported in the literature.